Mechanisms of Atherosclerosis Induced by Postprandial Lipemia - Zhao, Yixi; Liu, Longtao; Yang, Shengjie; Liu, Guijian; Pan, Limin; Gu, Chun; Wang, Yang; Li, Dan; Zhao, Ran; Wu, Min (Frontiers in Cardiovascular Medicine, 2021)
Postprandial lipemia plays an important role in the formation, occurrence, and development of atherosclerosis, and it is closely related to coronary heart disease and other diseases involving endothelial dysfunction, oxidative stress, inflammation, and other mechanisms; therefore, it has become a focus area for further research. The research progress regarding the influence of postprandial lipemia on endothelial function, oxidative stress and inflammation in patients was reviewed by referring to the relevant literature of the past 20 years.